Analysis of the Implications of Rapid Charging on Lithium-Ion Battery Performance. Issue 7 (29th April 2015) - Hasan, Mohammed F.; Chen, Chien-Fan; Shaffer, Christian E.; Mukherjee, Partha P.
Abstract : Fast charging is critical for efficient electrical vehicle operation. In this study, the fast charging performance limitations are elucidated with emphasis on the influence of temperature extremes. The role of charging protocols and electrode design parameters on charging time reduction are analyzed. Conventional charging protocol at high C-rate (e.g. at 3C) demonstrates that the performance limitation in rapid charging primarily originates from lithium ion transport in the electrolyte (electrolyte resistance) at moderate and high operating temperatures. However, interfacial kinetics resistance becomes the limiting mechanism for the 1C charging rate at low temperatures. To overcome the low temperature limitation, self-heating has been found to boost the cell performance and coulombic efficiency. An effective charging protocol has been suggested by maximizing lithium concentration at the anode/separator interface. Based on the advantageous combination of charging protocol and temperature, we propose a pulse-charging protocol with adiabatic operation, which can reduce charging time and increase performance. Furthermore, appropriate electrode design, such as reducing the electrode thickness and increasing the porosity, results in improved charging performance.